2021
DOI: 10.1039/d1ta02262h
|View full text |Cite
|
Sign up to set email alerts
|

Understanding multi-scale battery degradation with a macro-to-nano zoom through its hierarchy

Abstract: Lithium-ion battery (LIB) is featured by structural and chemical complexities across a broad range of length scales. Ultimately, it is the hierarchy of the battery structure that determines its functionality....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…The heterogeneous nature of electrochemical reactions and mechanical degradation places a daunting challenge in electron and X-ray characterizations. Recent large-scale electrode studies have uncovered that particle cracking is highly heterogeneous in composite electrodes. There are fundamental reasons and practical implications of such heterogeneity, which is ubiquitous even in the best-optimized commercial battery electrodes. , Figure exemplifies such heterogeneity in a section of a practical electrode containing thousands of active particles. In a well-prepared academic electrode (Figure a), the degree of damage heterogeneity is overwhelmingly significant.…”
mentioning
confidence: 99%
“…The heterogeneous nature of electrochemical reactions and mechanical degradation places a daunting challenge in electron and X-ray characterizations. Recent large-scale electrode studies have uncovered that particle cracking is highly heterogeneous in composite electrodes. There are fundamental reasons and practical implications of such heterogeneity, which is ubiquitous even in the best-optimized commercial battery electrodes. , Figure exemplifies such heterogeneity in a section of a practical electrode containing thousands of active particles. In a well-prepared academic electrode (Figure a), the degree of damage heterogeneity is overwhelmingly significant.…”
mentioning
confidence: 99%
“…Heterogeneity in cathode packing, the electrode polarization effect, and differences in particle size have been broadly reported. 43,44 The cause of heterogeneous performance can occur because of the interplay between the cathode and anode as observed in a previous study. 45 Improved performance in the cathode results in higher delithiation of the cathode, leading to higher lithiation of the anode after charge.…”
mentioning
confidence: 87%
“…Additionally, factors independent of both the cathode and anode such as separator porosity, electrolyte wetting, and uneven stack pressure can also influence local performance independent of the initial cathode and anode build. Local current heterogeneities have been linked to accelerated disintegration of cathode secondary particles and delamination of sections of the cathode . In large format cells, entire regions can underperform because of large-scale cell build defects .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[27][28][29][30] In the literature, X-ray tomography has been used to analyze the defects in commercial lithium batteries, to investigate different battery components, and to do so under extreme conditions, for example, high temperature, low temperature, ultra-fast charging, and thermal runaway. [31][32][33][34][35] Specific to Zn batteries, Yufit et al studied the Zn dendrite formation and dissolution in Zn-air battery using X-ray tomography and reported that the dendrite growth is promoted at the locations with high current density and with residual Zn deposits. The Zn dendrites can also be mechanically deformed by the separator, forming a more compact structure compared to the "open cell" scenario.…”
Section: Introductionmentioning
confidence: 99%